Degradation of muramyl dipeptide by mammalian serum. - Harrison, J (1985)
Muramyl dipeptide, N-acetylmuramyl-L-alanine-D-isoglutamine (MDP), is the minimal biologically active subunit of bacterial peptidoglycan and elicits an acute inflammation in vivo. We now report that MDP is degraded by normal rat serum into its constituents, N-acetylmuramic acid and L-alanine-D- isoglutamine. The dipeptide is further degraded into its components L-alanine and D-isoglutamine. These results may help to explain how inflammation elicited by MDP is terminated in vivo.